Fast production (ligitation) in the criminal process some Еuropean states (Journal of actual problems of jurisprudence, 2020)
Abstract. The article analyzes the legislative provisions and the practice of the functioning of theinstitution of pre-trial investigation of individual European states and the Republic of Kazakhstan underthe new Code of Criminal Procedure of the Republic of Kazakhstan in 2014. The main and additionalsigns of accelerated production are highlighted. Conclusions are drawn regarding the dominance ofthe organizational nature of the delimitation of inquiry on cases in which the preliminary investigationis not necessarily from the preliminary investigation itself. Subject of research are theoretical andorganizational areas. The development of differentiation of forms of criminal proceedings in the directionof simplification. Scientific novelty lies in the justification of further improvement of the nationalcriminal procedure legislation in the direction of strengthening procedural guarantees against unreasonablecharges and convictions, illegal restrictions on the rights and freedoms of man and citizen, aswell as ensuring a fair trial, strengthening the rule of law and forming a respectful attitudes to law, asexemplified by the experience of European states. When conducting the study, the author was basedon the provisions of the Constitution of the Republic of Kazakhstan, Code of Criminal Procedure of theRepublic of Kazakhstan.Key words: criminal procedure legislation, simplified production, pre-judicial investigation, preliminaryinvestigation, criminal legal proceedings.